Sense of Taste in the Gastrointestinal Tract - Ken Iwatsuki; Hisayuki Uneyama (Elsevier, 2012)
Recent advances in molecular biology have led to the investigation of the molecular mechanism by which chemicals such as odors and tastants are perceived by specific chemosensory organs. For example, G protein-coupled receptors expressed within the nasal epithelium and taste receptors in the oral cavity have been identified as odorant and taste receptors, respectively. However, there is much evidence to indicate that these chemosensory receptors are not restricted to primary chemosensory cells; they are also expressed and have function in other cells such as those in the airways and gastrointestinal (GI) tract. This short review describes the possible mechanisms by which taste signal transduction occurs in the oral cavity and tastants/nutrients are sensed in the GI tract by taste-like cells, mainly enteroendocrine and brush cells. Furthermore, it discusses the future perspectives of chemosensory studies. Keywords:: taste, taste cell, gastrointestinal tract, enteroendocrine cell, brush cell